(untitled) (Bangladesh Journal of Botany, 2021)
Genetics of Turcicum leaf blight (TLB) was to explore the mode of inheritance in maize caused by Exserohilum turcicum is a serious foliar disease. The genetics was estimated with the help of two crosses (CM 212 × V 336 and CM 212 × CM 145) from data of six generations (P1, P2, F1, F2, B1 and B2). The scaling tests as well as joint scaling tests revealed that the inadequacy of simple additive-dominance model and justifying the use of six parameter model for the detection of gene interactions in both the crosses for resistance to Turcicum leaf blight. All the scaling tests (A, B, C and D) were significant for the cross CM 212 × CM 145 and for the cross CM 212 × V 336 only A and C tests were significant. Based on the signs of [h] and [l] gene effects, complementary gene interaction for cross CM 212 × V 336 and duplicate gene interaction for cross CM 212 × CM 145 were evident in the inheritance of Turcicum leaf blight.